Pengaruh Upah Minimum Provinsi, PDRB, IPM, Jumlah Penduduk, TPAK Terhadap Penanaman Modal Asing Kabupaten/Kota di Provinsi Jawa Tengah - Choirunnisa, Ayu Maulidhia; Khoirudin, Rifki (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to look at the factors that influence foreign investment in 31 regencies/cities of Central Java Province in 2017-2022. The method used in the research is the GMM Two-Step analysis method. Based on the results of research conducted, it shows that the City Minimum Wage variable has a significant negative relationship with Foreign Investment. In the Gross Regional Domestic Product (GRDP) variable, there is a significant positive relationship with FDI. The HDI variable has no influence on PMA. The population variable does not have a significant relationship with FDI. There is a positive relationship between TPAK and FDI. Government policy to maintain and increase GRDP through the development of priority industries, improving infrastructure, as well as guaranteeing legal security and stability. And it is hoped that it can create a conducive environment for foreign investment, which will ultimately encourage sustainable economic growth in Central Java through the available workforce.